Comparative study of building plan approval between Peninsular Malaysia and Sarawak / Grace Jabu - Jabu, Grace (Faculty of Architecture, Planning and Surveying, 2013)
Malaysia was constituted in 16 September 1963 that consisting of Malaya State, Sabah, Sarawak and Singapore. Malaysia established to form political cooperation, economy and block communist influence. On august 1965, Singapore further appeared from Malaysia in order to be a republic (arkid.gov.com). After Malaya Federal has achieved independence in 1957, that make Sarawak start to discuss about their independence. Sarawak only enter Malaysia when is special protection to keep their interest such as law, services, custom such as are included in Federal Constitution Malaysia. Culture and Sarawak faith is different from peninsular Malaysia and rich with natural resources such as forest and petroleum. When Sarawak become one of Malaysia, Sarawak want to ensure freedom and control that all of that including Sarawak lifestyle. This is reason why Sarawak has special protection and more power in Federal Constitution Malaysia compared to peninsular Malaysia (malaysiabar.org.my). Although Sarawak has been a part of Malaysia but administration and legislation system that has been used between peninsular Malaysia and Sarawak very difference. That difference can see in town and planning system between Sarawak and peninsular Malaysia which Sarawak uses a land development legal system different with peninsular Malaysia.